New complexes of light lanthanides with the valsartan in the solid state: Thermal and spectroscopic studies - Ekawa, Bruno [UNESP]; Goncalves Nunes, Wilhan Donizete [UNESP]; Teixeira, Jose Augusto [UNESP]; Cebim, Marco Aurelio [UNESP]; Ionashiro, Elias Yuki; Caires, Flavio Junior [UNESP] (Elsevier B.V., 2018)
New lanthanides complexes with valsartan drug (H(2)Val) with stoichiometry Ln(2)(Val)(3)center dot nH(2)O (Ln = La, Ce, Pr, Nd and Sm) were obtained by reacting a solution of the lanthanide nitrate with a solution of valsartan sodium salt. The complexes were characterized by simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC) in dry air and nitrogen atmospheres, Evolved gas analysis (EGA) by TG-DSC-FTIR, Elemental Analysis (EA), complexometry with EDTA, Fourier transform Infrared and Raman (FTIR and FT-Raman) spectroscopy, UV vis spectroscopy and Powder X-Ray Diffraction (PXRD). The thermal decomposition of the complexes differed in dry air atmosphere with four steps for Ce, five for La and Pr and six for Nd and Sm. In nitrogen atmosphere all the complexes had a similar behavior, with three mass loss steps up to 1000 degrees C, leading to the formation of a mixture of carbonized material and metal oxide. The main gaseous products released during the thermal decomposition of these compounds were nitrous oxide, carbon dioxide and carbon monoxide (in air atmosphere), ammonia, nitrous oxide, carbon dioxide, carbon monoxide, and an unsaturated ketone or a mixture of unsaturated hydrocarbon and a ketone (in nitrogen atmosphere). The PXRD data suggest that the compounds are amorphous; the FTIR spectra suggests coordination of the ligand by the tetrazole ring, and by the carboxylate group as monodentate ligand; finally, the UV-vis spectra of the Pr, Nd and Sm complexes provided information about the degree of covalence of each compound.
Keywords: Light lanthanides; Valsartan; Thermal behavior; Pyrolysis; Evolved gas analysis